Atmospheric corrosion performance of wire rope sling in a sulfur dioxide-polluted environment. (June 2017) - Li, Shengli; Hu, Pengyue; Zhao, Xuefeng; Chen, Kejun; Li, Jinke
The straddle suspender of a suspension bridge is made up of wire ropes. The suspension bridges of cross-sea bridges are located in a marine atmospheric environment. Sulfur dioxide is an important component of this environment; it can increase the corrosion rate and result in suspender fracture. The corrosion mechanism of a steel wire is explained macroscopically and microscopically. As indicated in the digital images, scanning electron microscope, and X-ray diffractometer, the indoor experiment reacted faster in the first 6 days but slower after the 6th day. The experiment tended to stabilize from the 12th day to 15th day. The corrosion products in the low SO2 concentration condition are γ-FeOOH (lepidocrocite) and Fe3 O4 (magnetite) while products in the high SO2 concentration condition are γ-FeOOH (lepidocrocite), α-FeOOH (goethite), and Fe3 O4 (magnetite). The composition of the corrosion products did not change significantly from the 6th day to 12th day. The higher the SO2 concentration is, the more severe corrosion reacted on Fe. However, due to the effect of α-FeOOH, the Fe substrate was protected in the high SO2 environment. A high SO2 concentration generates more α-FeOOH. The tendency that the formula is exponential at both high and low SO2 concentration is similar.